(untitled) (Nepal Journal of Neuroscience, 2022)
In defiance with the meager tally of craniosynostosis, the surgical treatment of non syndromic craniosynostosis is one of the most common stratagem detained by craniofacial surgeon. By dint of the onerous anatomy secondary to the imperfection in embryogenesis, a long haul of drill is required to obtain perfection in surgical sequel.1 With the advancement in neurosurgical gadgetry and improvement in agility of neurosurgical authority, a multitude of strategy has evolved over time with the eminent intent to bring forth the supreme aftermath. Browsing through the archives of craniofacial reconstruction discloses vault remodeling techniques evolving over time with disparate modification tactics to the inception of state-of-the-art strategies like endoscopic suturectomy, spring treatment and cranial vault distraction osteogenesis.2 Regardless of all these alternatives, we still resort to the standard cranial vault remodeling with a fairly approving outcome. We herein attempt to disclose our result of vault remodeling in a series of patients with craniosynostosis.